Investigações e reflexões sobre implementação de metodologias ativas na educação básica - Fagundes, Laidines Seibel (2022)
This research investigated how the application of collaborative and peer-reviewed Active Methodologies can develop the construction of content, cognitive skills and attitudes in students. The present work used a qualitative approach, at different times it made use of documental research, action research and content analysis when investigating the application of Active Methodologies in Elementary and High School classes. Initially, the Class Diaries of an Elementary School Science teacher from 2013 to 2017 were analyzed to identify which resources were recorded and how the information released by the teacher could inform the use of Active Methodologies. The applications of Active Methodologies took place in the public school system with the classes that were under the regency of the researcher, being a ninth grade class of Elementary School (in 2019) and 13 high school classes during the COVID-19 pandemic. The proposed activities were supported by Digital Information and Communication Technologies (TDIC) and the themes were adapted to be in line with what the National Curricular Common Base advocates. In the different contexts in which they were applied, the activities contributed to the students' technological literacy, to the development of autonomy and encouraged the improvement of skills related to the ability to research, interpret, prepare texts, produce and use figures and graphs, as well as synthesis for data presentation and oral communication. In the application of all activities, one of the elements of analysis was the mediation process by the teacher to enable the performance of specific tasks and encourage students' autonomy in carrying out the work. We emphasize that the association of TDIC and Active Methodologies was positive and made possible conceptual, attitudinal and procedural learning, both in activities developed in person and in applications in virtual teaching. It is hoped that the results of this research will be an incentive for the application of proposals for activities that encourage the implementation of Active Methodologies that seek to develop student protagonism.